Coethnicity and Corruption: Field Experimental Evidence from Public Officials in Malawi. Issue 1 (2nd April 2020) - Seim, Brigitte; Robinson, Amanda Lea
Abstract: Corruption is widespread in many developing countries, though public officials' discretion in the solicitation of bribes may expose some citizens to more corruption than others. We derive expectations about how shared ethnicity between government officials and citizens should influence the likelihood of bribe solicitation. We evaluate these expectations through a field experiment in which Malawian confederates seek electricity connections from real government offices – an interaction that is often accompanied by bribe solicitation. Our field experiment exogenously varied coethnicity between the official and the confederate. We find that coethnicity increases the likelihood of expediting an electricity connection, both with and without a bribe, which we interpret as evidence of parochial corruption.